User experience and design thinking as a global trend in healthcare - Stola, Krzysztof (Journal of Medical Science, 2018)
Human-centered design describes a process and methodology that begins and ends with accommodating the needs and desires of our end users – the patients, families, providers, and other stakeholders, who each play a crucial role in the innovative healthcare creation process. Based on the desktop research it was found that human-centered design methodologies and tools are trending in the different fields and areas of healthcare design systems. It was found that customer-centric approach is the key fact of innovation creation process whether it is product or service, technology or organization level. The conclusion is that it is time for healthcare to start solving real people problems by implementing the human-centered approach in order to achieve high results and create innovative solutions that will match their customers and stakeholders needs and desires.